The formation of carbonic and silicon dioxide structured films through the decomposition of molecules on the surface of ionic crystals under the action of IR femtosecond laser radiation. (20th May 2016) - Kompanets, V O; Laptev, V B; Pigul'skii, S V; Ryabov, E A; Chekalin, S V; Blank, V D; Denisov, V N; Kravchuk, K S; Kulnitskiy, B A; Perezhogin, I A
Abstract: This study relates to the formation of carbon and silicon dioxide films that occurs as a result of the decomposition of organic and silicon-containing molecules on the surface of ionic crystals under IR femtosecond laser radiation of moderate intensity (~10 11 W cm −2 ) without molecular decomposition in the gas phase. We found that transparent graphite oxide films formed in the case of CO2 molecule decomposition.